Shade Selection, a Key to Esthetics - Shruti Deepak Jadhav; Varsha Sanjay Pandit; Ashwini Avinash Gaikwad; Vinaya Prabhanjan Ingale; Rajlaxmi Pradeep Patil; Mineet Satish Kaul (Journal of International Clinical Dental Research Organization)
One of the most difficult steps in restorative dentistry can be precisely matching natural teeth with an artificial restoration. Natural teeth come in a variety of shapes and hues. The type of shade guide, the person’s capacity for shade selection, and the circumstances surrounding the decision-making process all affect how accurate and dependable the process is. As a result, instrumental color determination must be incorporated into routine tasks. Many factors affect color matching, and when done incorrectly, it can lead to outcomes that are not satisfactory for the patient or the clinician. The following article sheds light on various methods of shade selection and which method is superior in matching the shade as close to that of the natural tooth color.